1998
DOI: 10.1088/0953-2048/11/10/033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the phase compositions at the final stage of heat treatment on the critical current density in Bi:2223/Ag tapes

Abstract: The effect of the phase compositions after the final stage of heat treatment on the critical current density in Bi:2223/Ag tapes has been investigated. A high volume fraction of Bi:2223 has been considered the most critical factor in achieving a high ; however, it is extremely difficult to attain pure Bi:2223 phase via routine thermomechanical processing. Although a higher volume fraction of Bi:2223 phase can be attained using a higher processing temperature, it is always found to co-exist with Bi:2201 which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…But for only 20 h of reaction at 850 • C, the main peaks from the Sr 14 Cu 24 O 41 (or 14, 24) phase are strong. This result confirms conclusions of the paper by Giannini et al [27] in which it is shown that the formation of (14,24) is fast at a high temperature. During the heating step, the (14,24) phase content increases and saturates when the dwell temperature is attained.…”
Section: Study Of Discs Textured Via Process Csupporting
confidence: 92%
See 2 more Smart Citations
“…But for only 20 h of reaction at 850 • C, the main peaks from the Sr 14 Cu 24 O 41 (or 14, 24) phase are strong. This result confirms conclusions of the paper by Giannini et al [27] in which it is shown that the formation of (14,24) is fast at a high temperature. During the heating step, the (14,24) phase content increases and saturates when the dwell temperature is attained.…”
Section: Study Of Discs Textured Via Process Csupporting
confidence: 92%
“…This result confirms conclusions of the paper by Giannini et al [27] in which it is shown that the formation of (14,24) is fast at a high temperature. During the heating step, the (14,24) phase content increases and saturates when the dwell temperature is attained. Maintaining the temperature constant then induces a decrease in (14,24) phase.…”
Section: Study Of Discs Textured Via Process Csupporting
confidence: 92%
See 1 more Smart Citation
“…Superconducting coupling between superconducting crystalline grain boundaries in the Bi-based ceramics is very weak [3]. The presence of non-superconducting phases (such as Cu 2 O) in the investigated samples and the presence of Bi 3+ , Ca 2+ or Cu 2+ at the grain boundaries can limit weak coupling between superconducting grains [9][10][11]. This could lead to some differences between T c values of the samples and the broadening of the superconducting transition.…”
Section: Resultsmentioning
confidence: 95%
“…Some of them, commonly listed in the literature, are: grain quality and connectivity (weak links), pinning centres, stoichiometry of the 2223 phase, grain size, etc. The precise stoichiometry of the 2223 phase, as stated by many authors [9,[10][11][12][13], is an essential parameter. Lead is the one of the elements whose loss during sintering has been reported most frequently for tapes [12,13] as well as for bulk samples [14,15].…”
Section: Resultsmentioning
confidence: 99%